أحكام التعويض عن إصابات العمل وفقا للقانون واتجاهات القضاء: دراسة تحليلية مقارنة - د.عبدالرحمناحمدالمساعد (White Nile Journal for Studies and Research, 2020)
The study “Work Injury Compensation” in Legislations, derives its significance from the inter-weaved issues to which ,many people are not acquainted. This is in addition to its role in the socio-economical life as well as the stability of the community’s relationships. Despite the fact that the work injury compensation rules being subject to social insurance law is better for the worker than exposing the employee to civilian responsibilities, yet, the worker social protection provided by the social insurance law is very limited. Work injury is one of the most controversial risks that workers contemplate on. It is also a fertile field for problems associated with work factors versus legislation acts. On the other hand, both employer and employees do not seem to be well oriented about the need to enforce social regulations thereby leading to lack of cooperation between the concerned parties including the official work agencies which are responsible for social regulations enforcement. Consequently, a large portion of the social legislations have become dormant. The inefficiency of these regulations can be attributed to own inadequacy or to shortcomings of the work agencies in providing workers with real protection.. misleadingly superficial In light of all these controversies, this research has scrutinized work and insurance laws applied in Sudan in contrast with some Arabian and foreign laws. This research was started by a detailed overview reflecting the historic evolution in terms of work injuries compensation. It sheds light on the initial commencement of Sudanese work legislations. It also displays the historic process of work injuries compensations. After having reviewed the overall Sudanese injuries compensation laws, the research conducts an in depth investigation on the concept of work injury as such. The other aspect in this research deals with the notion of work injury compensation, types and causes. The research also projects merits of the insurance coverage that an injured worker may avail. It further discusses the procedural formalities of work injuries compensation and the agencies which are legally responsible to enact the relevant regulations in terms of estimating the disability rate as well as settlement of disputes at courts and the social insurance organization. At a certain stage, statistics has been arranged on funds paid by the social